Adult-onset cerebello-brainstem-dominant form of X-linked adrenoleukodystrophy with auditory pathway involvement: A case report - Yokota, Yusuke; Minami, Akihiko; Kawase, Kango; Taniguchi, Takanori; Okubo, Gosuke; Shinde, Akiyo; Kanao, Shotaro; Kubo, Takeshi; Suenaga, Toshihiko; Yasumura, Sumika; Suzuki, Mizue; Ota, Rie; et al. (Tenri Medical Bulletin, 2024)
X-linked adrenoleukodystrophy (X-ALD) is classified into several clinical subtypes. Among them, the cerebello-brainstem-dominant form is rare, and its symptoms and imaging findings can mimic spinocerebellar degeneration (SCD), making diagnosis difficult. Herein, we report a case that we initially diagnosed as SCD but was eventually diagnosed as the cerebello-brainstem-dominant form of X-ALD. The patient presented with psychiatric symptoms in adulthood. He subsequently developed gait disturbance and was referred to the neurology department of our hospital. Initial magnetic resonance imaging (MRI) showed atrophy of the cerebellum and pons, and abnormal signals in various regions, including the middle cerebellar peduncles, the corpus callosum, infero-posterior part of the bilateral thalami, and lateral edges of the midbrain, on T2-weighted imaging. The patient was followed up as SCD; however, his symptoms and MRI findings worsened. Further examination was performed, and the diagnosis of X-ALD was made. Abnormal signals in the thalami and midbrain on MRI are considered to correspond to the medial geniculate bodies and the brachia of the inferior colliculus, respectively. They constitute the auditory pathway, which is an evaluation item in Loes score, an imaging-based scoring system for patients with X-ALD. Recognizing abnormalities in the bilateral auditory pathway may aid accurate diagnosis of X-ALD.